DOI: 10.31274/rtd-180813-9323
|View full text |Cite
|
Sign up to set email alerts
|

Rating teacher performance to determine career ladder advancement: An analysis of bias and reliability

Abstract: Internal consistency of the appraisal Instrument 80 Effect of rater characteristics on teacher appraisal scores 81 Inter-rater agreement 82 Intra-rater agreement 83 Conclusions 83 Limitations 85 Discussion 86 Impact on career ladder Implementation 97 Recommendations for Practitioners 101 Recommendations for Further Research 103 BIBLIOGRAPHY 105 ACKNOWLEDGMENTS 117a APPENDIX A. TEACHER APPRAISAL SYSTEM 118 Philosophy of Education 119

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Standards have long been a topic of study. At least six Iowa State University researchers sought to contribute knowledge in this area (Cameron, 1973;Garcia, 1980;Rucker, 1981;Westerberg, 1983;Harrington, 1984;and Peterson, 1988). How one monitors and reports progress has been the topic of another group of researchers (Edwards, 1985;Semones, 1987;Stevenson, 1987;Floden, 1987;and Wicks, 1988).…”
Section: Historical Considerationsmentioning
confidence: 99%
“…Standards have long been a topic of study. At least six Iowa State University researchers sought to contribute knowledge in this area (Cameron, 1973;Garcia, 1980;Rucker, 1981;Westerberg, 1983;Harrington, 1984;and Peterson, 1988). How one monitors and reports progress has been the topic of another group of researchers (Edwards, 1985;Semones, 1987;Stevenson, 1987;Floden, 1987;and Wicks, 1988).…”
Section: Historical Considerationsmentioning
confidence: 99%
“…That is to say, evaluators may have a bias based on, among other things, their own gender or the gender of the teacher (IEATP, Participant Manual, Fall, 2002;Peterson, 1998). Peterson (1988) also indicated that female evaluators gave significantly lower ratings than male evaluators, as did evaluators of different racial groups.…”
Section: Gender Bias In Teacher Evaluationmentioning
confidence: 92%
“…It is worth noting that other important interactions may not have been included in this study. This would be underscored by the lack of sphericity that has been observed as well as the possibility of other interactions such as race (Brown, 2005), career stage of the evaluator (Peterson, 1988), or subject area being observed (Ward & Sistrunk, 1988). More specific thoughts related to gender interaction findings will be addressed in the final section of the study.…”
Section: Comparison Of Gender Differencesmentioning
confidence: 99%
“…The mean score for these outside appraisers was lower than the mean rating assigned by the teachers' own building principals. This shows the tendency for leniency in the ratings of evaluators having ongoing relationships with appraisees (Peterson, 1988).…”
Section: Leniency In Performance Appraisalsmentioning
confidence: 94%